PENGARUH PENGAWASAN SUMBER DAYA MANUSIA, BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP DISIPLIN KERJA KARYAWAN PADA LEMBAGA PERKREDITAN DESA (LPD) DESA ADAT KEDONGANAN - Ni Ketut Ratna Parmitha Dewi; Nengah Landra; Ni Made Dwi Puspitawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
This study aims to determine the effect of monitoring human resources, organizational culture and job satisfaction partially and simultaneously on work discipline. The location of this research is in the Lpd of the Kedonganan traditional village. The population uses Lpd Kedonganan traditional village employees and a sample of 40 employees. The data analysis technique uses Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Correlation Test, Coefficient of Determination Test, F Test and t Test. From the results of the study, it was found that (1) human resource supervision had a significant positive effect on work discipline, (2) organizational culture had a significant positive effect on work discipline, (3) job satisfaction had a significant positive effect on work discipline, (4) simultaneously supervised resources. human resources, job satisfaction and job satisfaction have a significant effect on work discipline. The suggestion that can be given by researchers is that the leader of the Village Credit Institution (LPD) of the Kedonganan Traditional Village should be firm in giving warnings, sanctions and punishments to employees who make mistakes at work. (LPD) Kedonganan Traditional Village should provide training or guide employees and increase the amount of wages given to employees.